Identification of Deep Defects by Positron Annihilation Spectroscopy in Annealed GaAs Thin Films (Latakia University Journal -Basic Sciences Series, 2021)
Positron annihilation spectroscopy was applied to investigate the defect properties in GaAs thin films at different annealing temperature. Positron lifetime and Doppler broadening spectroscopy using mono-energetic positron beam were used to identify the defects in the GaAs films. Theoretical calculations of the positron lifetime were performed. DBS measurements showed, that with increasing the annealing temperature increases the deep defect density. Lifetime measurements confirmed this result. The decomposition of the lifetime spectra of the samples resulted in the detection of two vacancy-related defects: a vacancy 3  or 3  (annealing temperature is less than 650 K) and a negatively charged vacancy complex  (annealing temperature is more than 650 K). Furthermore, Lifetime measurements interpreted the presence of large cluster of vacancies by the near-surface defective regions.